Physical-Mechanical Properties of Edible Film Based on Beneng Taro (Xanthosoma Undipes K.Koch) Starch with Plasticizer - Serly Eka Puspita; Fitria Riany Eris; Rifqi Ahmad Riyanto (University of Sultan Ageng Tirtayasa, 2022)
Edible film is a thin layer as a coating for foodstuffs made from edible materials such as taro. One of the taro tubers variety that can be used as edible film is Beneng from Banten. Edible films made from starch have a weakness that is easy to tear and have low elasticity, to change the physical properties of the film from starch it is necessary to add a plasticizer. Plasticizers that are often added to the production of edible films are xylitol, sorbitol, polyethylene glycol, and glycerol. The purpose of this study was to determine the effect of the type of treatment and concentration of plasticizer on the physical-mechanical properties of edible film made from taro beneng starch. The treatment in this study was divided into 2 factors, the first factor was the type of plasticizer (sorbitol, glycerol and PEG), while the second factor was the concentration of the plasticizer (1%, 3%, and 5%). The tests carried out in this study were the tensile strength, elongation, thickness, water vapor transmission, and water solubility tests. The results showed that the type and concentration of plasticizer have a significant effect on the characteristics of the edible film. The interaction between the type and concentration of plasticizer has no significant effect on the water vapor transmission test. The best edible film in this study was the edible film with the addition of the plasticizer sorbitol with a concentration of 3%.